2012
DOI: 10.1089/jwh.2011.2872
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Health and Employment in Mature Women: A Longitudinal Study

Abstract: Background: Despite a reduction in income inequalities between men and women, there is still a large gap between income and retirement savings of Australian men and women. This is especially true for women who have health or disability problems. Mature age women are closest to retirement and, therefore, have less chance than younger women to build up enough retirement savings and may need to continue working to fund their older age. Continued workforce participation may be particularly difficult for women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…33 The impact may be greater for women, who on average work for fewer years than men do. 34 The economic implications of diabetes might also be relevant for employers, who face costs from diabetic workers through productivity losses medical claims and disability benefits. 29 On a national level, the financial losses are considerable.…”
Section: Discussionmentioning
confidence: 99%
“…33 The impact may be greater for women, who on average work for fewer years than men do. 34 The economic implications of diabetes might also be relevant for employers, who face costs from diabetic workers through productivity losses medical claims and disability benefits. 29 On a national level, the financial losses are considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Poor health among women has not only generational repercussions, but also implications for contemporaneous labor force participation, productivity, earnings, family income, and economic wellbeing. When looking at labor force participation, a longitudinal study from Australia found that having diabetes, high blood pressure, or psychiatric conditions decreased the likelihood of women’s employment [ 147 ]. Globally, only 52% of the world’s adult women participate in the labor market, 26% lower than men.…”
Section: Resultsmentioning
confidence: 99%
“…The data such as body-mass index (BMI) (LBP increases with raised BMI 2 ); races (Asians have higher acceptance of ACU and greater reluctance to use Western medicine, 3 and their BMI is lower than that of other ethnic groups 4 ); day of sick leave for LBP (an ACU practitioner is not able to issue a sick leave certification in Canada, if a patient wanting a medical absence or malingering would only visit a GP); employment (unemployed patients may be more financially restricted, and tend to spend less on food 5 and not consider ACU treatment that is not covered through the public health system in Canada).…”
Section: Clinical Demographic and Social Characteristicsmentioning
confidence: 99%